Production method for inhibiting martensite transformation in 80-grade tire cord steel wire rod
By combining the casting blank with the pressing process and the cooling control process, the formation of martensite in the 80-level cord steel strips is suppressed, and the poor processing performance and high cost problems caused by martensite transformation are solved, and high quality is achieved steel cord production.
Patent Information
- Application Number
- CN202411835939.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-12-13
AI Technical Summary
In the production process of 80-level cord steel coils, the transformation of martensite structure leads to poor processing performance and high cost. It is difficult for existing processes to effectively inhibit the formation of martensite, affecting the material yield and processing cost of steel cords.
Using medium-sized rectangular billet combined with casting billet pressing technology, the segregation and cooling speed of the casting billet are controlled through one-fire straight rolling, head-off rolling and cold control technology, the formation of martensite is suppressed, and the drawing performance of steel cords is improved. .
High-quality production of 80-level cord steel coils has been achieved, with martensite structure of level 0, low central segregation, less grain boundary cementite, improved tensile strength, wet-pull wire breaking rate and twisted wire breaking rate , the cost is within an acceptable range.
Smart Images

Figure CN119307802A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cord steel wire rod production, in particular to a production method for suppressing martensitic transformation in a grade 80 cord steel wire rod. Background Art
[0002] Steel cord is a high-tech wire product. Its production equipment is expensive and the process is complex, making it one of the most demanding wire products. During processing, steel cord undergoes a series of deformations, including stretching, torsion, and bending. During tire service, it withstands combined bending and stretching loads, as well as impact loads. Therefore, the quality of the raw wire rod plays a decisive role in the processing and performance of the steel cord.
[0003] Martensite is a hard and brittle phase structure. It does not deform along with the matrix structure during the drawing process of the cord steel wire rod. As the drawing continues, cracks will initiate in front and behind the martensite and continue to expand, eventually leading to wire breakage. Therefore, martensite is a structure that must be eliminated in the cord steel wire rod.
[0004] When producing high-strength steel cord and some ultra-high-strength steel cords, Grade 80 steel wire rod is used. Inadequate tooling or improper process control can lead to severe center segregation in the ingot. This center segregation zone contains significant concentrations of C and Mn, with their contents far exceeding the average matrix composition. To prevent carbon precipitation in this area after rolling, a forced cooling process is commonly used. However, this introduces the risk of martensitic transformation, severely impacting drawing performance.
[0005] Currently, the industry uses two processes for producing this type of wire rod: the billet process and the large-scale billet process. With billet continuous casting, due to its small size, even with electromagnetic stirring and billet reduction technology, it is still impossible to ensure low segregation and stability of the billet. This results in center segregation of the wire rod after rolling, and large fluctuations in the network cementite and martensite. This cannot meet the high compression deformation requirements of the steel cord processing process, making it prone to pull-out fracture or strand breakage. The wire fracture often exhibits a central burr, significantly impacting the yield rate and processing cost of the steel cord. With large-scale billet continuous casting, the combination of continuous casting and weak cooling combined with billet reduction can significantly improve the center segregation of the billet. However, the billet must undergo two heating and rolling processes to obtain the required specifications of the cord steel wire rod. This process is long, costly, and economical, making it uncompetitive in the market. Summary of the Invention
[0006] In view of this, the purpose of the present invention is to propose a production method for inhibiting the martensitic transformation in 80-grade cord steel wire rod, which adopts a medium-sized rectangular billet combined with a casting billet reduction process, and adopts a single-fire direct rolling, head-off rolling and a unique post-rolling controlled cooling process, which can not only improve the segregation of the casting billet and avoid the increase in production costs, but also inhibit the formation of martensitic structure, so that the 80-grade cord steel wire rod has good product quality and drawing processing performance.
[0007] Based on the above-mentioned purpose, the present invention provides a production method for inhibiting martensitic transformation in 80-grade cord steel wire rod, comprising the following steps: molten iron pretreatment → converter smelting → LF refining → continuous casting → heating → controlled rolling → controlled cooling; the continuous casting process adopts electromagnetic stirring combined with a heavy reduction process for the cast billet, and the total reduction under heavy pressure is controlled to reach 9-11%, and the carbon segregation index of the continuous casting billet is 0.98-1.08; the controlled rolling adopts a headless billet opening machine added before the roughing mill, and the billet is first rolled into an intermediate billet, and then enters the roughing mill into a single-fire direct rolling process; in the controlled cooling process, the cooling rates before, during and after the phase change are controlled to be 20-25°C / s, 3-8°C / s and ≤3°C / s, respectively.
[0008] During the continuous casting process, the continuous casting speed is controlled at 1.25-1.35m / min, and the superheat is controlled at 15-25°C. The current of the electromagnetic stirring of the crystallizer is 580-620A and the frequency is 2-4Hz, and the current of the end electromagnetic stirring is 490-510A and the frequency is 11-13Hz. The secondary cooling adopts a weak cooling process, and the specific water volume is controlled at 0.25-0.30L / kg. The area of the equiaxed crystal zone of the ingot accounts for 65-75%, and the central shrinkage cavity is 0-0.5. The ingot passes through 10 sets of tension and straightening rollers, and the total reduction under heavy pressure reaches 9-11%. The reduction passes and reductions are 0 / 0 / 0 / 3 / 3 / 3 / 4 / 5 / 0 / 0mm and 0 / 0 / 0 / 3 / 4 / 4 / 5 / 6 / 0 / 0mm respectively. After heavy pressure, the size of the ingot is 182×244-178×246mm. Low-magnification inspection of the ingot revealed no central cracks. The continuous casting process utilizes electromagnetic stirring in the mold, electromagnetic stirring at the end of solidification, and heavy reduction technology to produce medium-sized rectangular ingots. Low superheat control, a secondary cooling process, and appropriate casting speed control prevent the formation of central cracks during ingot straightening and reduction. The chemical composition of the central mushy zone is also homogenized, maximizing the dispersion and shrinkage feeding of the central molten steel, avoiding the formation of central shrinkage cavities and central component segregation zones, and creating favorable matrix conditions for controlling the wire rod structure.
[0009] During the controlled rolling process, the descaling pressure is controlled to be ≥20MPa, and 4 headless blanking machines are added in front of the rough rolling mill. The starting rolling temperature is 1020-1120℃, the finishing rolling temperature is 900-930℃, and the sizing temperature is 900-930℃. A high-power descaling machine is used in the rolling process to increase the descaling water pressure to above 20MPa, which can cleanly remove the iron oxide scale on the surface of the billet and avoid surface defects caused by the pressing of iron oxide scale on the surface of the rolled piece and the finished product. Due to the large billet shape, in order to reduce the cost of the rolling process, a one-fire direct rolling technology is adopted, that is, 4 headless blanking machines are added in front of the traditional rough rolling mill to roll the 182×244-178×246 rectangular billets into 160×160mm intermediate billets, and then enter the traditional rough rolling mill group.
[0010] During the controlled cooling process, the wire rod extrusion temperature is controlled at 915-945°C, the initial roller speed is 1.10m / s, and the rated air volume of the fan is 280000m 3 / h. The air volume of the first four fans is 75% of their rated air volume, the air volume of the fifth fan is 65% of their rated air volume, the air volume of the sixth fan is 50% of their rated air volume, and the air volume of the seventh and eighth fans is 40% of their rated air volume. The remaining fans are turned off. When the wire rod temperature drops below 580°C, a heat shield is installed. The post-rolling controlled cooling process uses an axial flow high-pressure air distribution arrangement. Combined with adjustments to the Jialing device, the roller speed and fan air volume settings are coordinated to increase the cooling rate of the wire rod before the phase transformation after spinning, inhibiting the precipitation of network proeutectoid cementite; reduce the cooling rate during and after the phase transformation to inhibit the formation of martensite; and install a heat shield when the wire rod temperature drops below 580°C to fully release the phase transformation stress and shorten the natural aging period. During the controlled cooling process, the cooling rates before, during, and after the phase transformation are controlled to be 20-25°C / s, 3-8°C / s, and ≤3°C / s, respectively.
[0011] The hot metal pretreatment process uses hot metal and undergoes a pre-desulfurization process to control sulfur content to ≤ 0.005% and titanium content to ≤ 0.03%. The converter uses a double-slag process to control phosphorus content to ≤ 0.008%. All scrap steel is clean, produced in-house, to minimize the introduction of harmful and residual elements.
[0012] The converter smelting adopts a high carbon drawing method, and controls the tapped steel C≥0.15%, O≤0.050%, P≤0.008%, and S≤0.010%.
[0013] During the LF refining process, a double slag method is used to promote the plasticization of inclusions. The first slag making controls the slag basicity to 2.5-3.0; the second slag making controls the slag basicity to 0.7-0.9; the argon flow rate during soft blowing is 55-58L / min, and the soft blowing time is ≥60min. The refining process uses magnesium-carbon refractory materials and low-aluminum, low-titanium alloy auxiliary materials to reduce the generation of alumina inclusions and titanium inclusions. Long-term soft blowing is used to fully stir the molten steel so that the inclusions aggregate, grow, float up and are removed. At the same time, the double slag method is used to promote the plasticization of inclusions, so that the inclusions extend as the matrix deforms during the hot rolling and cold drawing processes of the wire rod, thereby improving the deep drawing performance of the wire rod and reducing the risk of wire breakage during drawing.
[0014] The temperature of the second heating section is 950-1080°C, and the temperature of the soaking section is 1060-1160°C. The heating time of the second heating section and the soaking section is guaranteed to be no less than 100 minutes, the furnace pressure is no less than 15 Pa, and the residual oxygen content is 0.5-2.0%.
[0015] The chemical composition of the 80 grade cord steel wire rod includes, by mass percentage, C: 0.80-0.85%, Si: 0.25-0.30%, Mn: 0.40-0.45%, S≤0.008%, P≤0.010%, Al≤0.002%, Ti≤0.001%, O≤0.0015%, N≤0.0035%, and the rest are Fe and unavoidable impurity elements.
[0016] The beneficial effects of the present invention are as follows: the martensitic structure of the 80-grade steel cord wire rod produced by the present invention is Grade 0, the proportion of central segregation ≤ Grade 1 reaches 100%, the proportion of grain boundary cementite ≤ Grade 1 reaches 100%, the total decarburization depth is 0, the total decarburization depth is ≤30μm, the sorbite ratio is ≥80%, the surface defect and scale penetration depth is ≤0.03mm, the wire rod inclusion purity is ≤0.02%, and the tensile strength difference within the same turn is ≤40MPa. In actual production of φ0.30mm ultra-high-strength steel cord, the wet-drawing breakage rate is less than 0.8 times / ton, and the stranding breakage rate is less than 2 times / ton, which exceeds the actual quality level of the benchmark supplier. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0018] Figure 1 This is a schematic diagram of the metallographic structure of Example 1 of the present invention, in which no martensite is found; Figure 2Schematic diagram of the metallographic structure of Comparative Example 1, showing level 3 martensite; Figure 3 Schematic diagram of wire rod segregation in Example 1 of the present invention, where the center segregation is level 0; Figure 4 Schematic diagram of wire rod segregation in comparative example 1, with a center segregation of level 1.5. DETAILED DESCRIPTION
[0019] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to specific embodiments.
[0020] It should be noted that, unless otherwise defined, the technical or scientific terms used in the present invention should have the common meanings understood by persons having ordinary skills in the field to which the present invention belongs.
[0021] The present invention uses molten iron and undergoes a pre-desulfurization process. The converter uses self-produced clean scrap steel to reduce harmful elements in the steel. The purity of the molten steel is improved through smelting control, slag blocking and tapping, residual steel operation, and refractory and alloy auxiliary materials, combined with inclusion plasticization technology. The continuous casting process uses electromagnetic stirring combined with medium-shaped billet heavy reduction technology, combined with single-fire direct rolling technology, head-off rolling technology, and precise control of cooling rates before, during, and after phase transformation to suppress the generation of center network carbon and martensite, thereby obtaining 80-grade cord steel wire rod with excellent deep drawing performance. The present invention is described in detail below with reference to embodiments. Example 1
[0022] Chemical composition of wire rod: by mass percentage, C: 0.83%, Si: 0.26%, Mn: 0.42%, S: 0.006%, P: 0.009%, Al: 0.0014%, Ti: 0.0005%, O: 0.0011%, N: 0.0022%, and the rest are Fe and unavoidable impurity elements.
[0023] Hot metal pretreatment: Use hot metal and pre-desulfurize it, and the hot metal entering the furnace has S: 0.004% and Ti: 0.025%.
[0024] Converter smelting: All scrap steel is self-produced clean scrap steel, with 35 tons of scrap added. High-carbon technology is used, and the steel produced has C: 0.18%, O: 0.043%, P: 0.007%, and S: 0.004%.
[0025] Refining: LF refining uses magnesium-carbon refractory materials and low-aluminum, low-titanium alloy auxiliary materials to reduce alumina and titanium inclusions. A dual-slag method is used to promote plasticization of inclusions. The high-basicity slag has a basicity of 2.7, and the low-basicity slag has a basicity of 0.85. The argon flow rate during soft blowing is 57 L / min, and the soft blowing time is 64 minutes.
[0026] Continuous Casting: The continuous casting process utilizes electromagnetic stirring in the mold, electromagnetic stirring at the end of solidification, and heavy reduction technology. The mold copper tube has internal dimensions of a 200mm×240mm rectangular billet cross-section. Casting is performed using an integral nozzle, with a continuous casting speed of 1.30m / min and a superheat of 18-22°C. The mold electromagnetic stirring current is 600A at a frequency of 3Hz, and the end electromagnetic stirring current is 500A at a frequency of 12Hz. A weak cooling process is used for the secondary cooling process, with a specific water volume of 0.28L / kg. The billet passes through 10 sets of straightening rollers, achieving a total heavy reduction of 11%. The reduction passes and reductions are 0 / 0 / 0 / 3 / 4 / 4 / 5 / 6 / 0 / 0mm, respectively. The final billet dimensions after heavy reduction are 178×246mm. Low-magnification examination of the billet reveals no central cracks, an equiaxed crystal area of 72%, and a central shrinkage cavity of level 0. Drilling analysis reveals a carbon segregation index of 1.06.
[0027] Heating: The temperature of the second heating section of the walking beam heating furnace is 1054-1075℃, the temperature of the soaking section is 1097~1122℃, the heating time of the second heating section and the soaking section is 123min in total, the furnace pressure is 16-23Pa, and the residual oxygen content is 0.8-1.7%.
[0028] Rolling: After heating, the billets are descaled with high-pressure water at a pressure of 21 MPa to remove surface oxide scale. The descaled 178×246 mm rectangular billets are rolled into 160×160 mm intermediate billets using four headless blooming mills before entering a conventional roughing mill. The initial rolling temperature is 1032-1064°C, the finishing rolling temperature is 912-926°C, and the sizing temperature is 915-928°C.
[0029] Controlled cooling: spinning temperature 918-932℃, roller initial speed 1.10m / s, fan air volume 280000m 3 / h, with the air volumes of fans 1-8 set at 75% / 75% / 75% / 75% / 65% / 50% / 40% / 40% respectively, and the remaining fans turned off. The wire rod temperature at the 12th insulation cover was 563°C. The measured average cooling rates before, during, and after the phase transition were 22.8°C / s, 5.5°C / s, and 2.8°C / s, respectively.
[0030] Inspection results: 100% of the wire rod possesses martensite at level 0, 100% of central segregation at levels 0-1, 100% of grain boundary cementite at levels 0-1, a full decarburization depth of 0, a total decarburization depth of 20-35μm, 85% of sorbite, 0-0.03mm penetration depth of surface defects and scale, 0.006% wire rod inclusion purity, and a tensile strength difference of 28MPa within the same coil. In the production of φ0.30mm ultra-high-strength steel cord, the total breakage rate for wet-drawn steel cord was 0.7 times / ton, and the total breakage rate for stranded steel cord was 1.8 times / ton. Example 2
[0031] Chemical composition of wire rod: by mass percentage, C: 0.81%, Si: 0.27%, Mn: 0.43%, S: 0.005%, P: 0.010%, Al: 0.0008%, Ti: 0.0004%, O: 0.0009%, N: 0.0023%, and the rest are Fe and unavoidable impurity elements.
[0032] Hot metal pretreatment: Use hot metal and pre-desulfurize it, and the hot metal entering the furnace has S: 0.005% and Ti: 0.022%.
[0033] Converter smelting: All scrap steel is self-produced clean scrap steel, with 32 tons of scrap added. High-carbon technology is used, and the steel produced has C: 0.16%, O: 0.047%, P: 0.009%, and S: 0.006%.
[0034] Refining: LF refining uses magnesium-carbon refractory materials and low-aluminum, low-titanium alloy auxiliary materials to reduce alumina and titanium inclusions. A dual-slag method is used to promote plasticization of inclusions. The high-basicity slag has a basicity of 2.6, and the low-basicity slag has a basicity of 0.9. The argon flow rate during soft blowing is 66 L / min, and the soft blowing time is 58 minutes.
[0035] Continuous Casting: The continuous casting process utilizes electromagnetic stirring in the mold, electromagnetic stirring at the end of solidification, and heavy reduction technology. The mold copper tube has internal dimensions of a 200mm×240mm rectangular billet cross-section. Casting is performed using an integral nozzle. The continuous casting speed is 1.30m / min, and the superheat is 19-24°C. The mold electromagnetic stirring current is 600A at a frequency of 3Hz, and the end electromagnetic stirring current is 500A at a frequency of 12Hz. A weak cooling process is used for the secondary cooling process, with a specific water volume of 0.28L / kg. The billet passes through 10 sets of straightening rollers, achieving a total heavy reduction of 11%. The reduction passes and reductions are 0 / 0 / 0 / 3 / 3 / 3 / 4 / 5 / 0 / 0mm, respectively. The final billet dimensions after heavy reduction are 182×244mm. Low-magnification examination of the billet reveals no central cracks, an equiaxed crystal area of 70%, and a central shrinkage cavity of level 0. Drilling analysis reveals a carbon segregation index of 1.04.
[0036] Heating: The temperature of the second heating section of the walking beam heating furnace is 1032-1061°C, the temperature of the soaking section is 1086-1115°C, the heating time of the second heating section and the soaking section is 126 minutes in total, the furnace pressure is 18-25Pa, and the residual oxygen content is 0.6-1.9%.
[0037] Rolling: After heating, the billets are descaled with high-pressure water at a pressure of 21 MPa to remove surface oxide scale. The descaled 182×244 mm rectangular billets are rolled into 160×160 mm intermediate billets using four headless blooming mills before entering a conventional roughing mill. The initial rolling temperature is 1022-1055°C, the finishing rolling temperature is 907-921°C, and the sizing temperature is 913-928°C.
[0038] Controlled cooling: spinning temperature 920-937℃, roller initial speed 1.10m / s, fan air volume 280000m 3 / h, with the air volumes of fans 1-8 set at 75% / 75% / 75% / 75% / 65% / 50% / 40% / 40% respectively, and the remaining fans turned off. The wire rod temperature at the 12th insulation cover was 571°C. The measured average cooling rates before, during, and after the phase transition were 23.2°C / s, 4.6°C / s, and 2.4°C / s, respectively.
[0039] Inspection results: 100% wire rod martensite, 100% central segregation, 100% grain boundary cementite, 0% grain boundary cementite, 0% total decarburization depth, 0% total decarburization depth, 20-30μm total decarburization depth, 85% sorbite, 0-0.03mm depth of surface defects and scale penetration, 0.009% wire rod inclusion purity, and 36MPa tensile strength difference within the same turn. In the production of φ0.30mm ultra-high-strength steel cord, the total wire breakage rate in wet-drawing was 0.6 times / ton, and the total wire breakage rate in stranding was 1.7 times / ton. Example 3
[0040] Chemical composition of wire rod: by mass percentage, C: 0.82%, Si: 0.26%, Mn: 0.44%, S: 0.007%, P: 0.008%, Al: 0.0011%, Ti: 0.0006%, O: 0.0012%, N: 0.0021%, and the rest are Fe and unavoidable impurity elements.
[0041] Hot metal pretreatment: Use hot metal and pre-desulfurize it, and the hot metal entering the furnace has S: 0.004% and Ti: 0.020%.
[0042] Converter smelting: All scrap steel is self-produced clean scrap steel, with 32 tons of scrap added. High-carbon technology is used, and the steel produced has C: 0.21%, O: 0.035%, P: 0.008%, and S: 0.007%.
[0043] Refining: LF refining uses magnesium-carbon refractory materials and low-aluminum, low-titanium alloy auxiliary materials to reduce alumina and titanium inclusions. A double-slag method is used to promote plasticization of inclusions. The high-basicity slag has a basicity of 2.8, and the low-basicity slag has a basicity of 0.8. The argon flow rate during soft blowing is 58 L / min, and the soft blowing time is 65 minutes.
[0044] Continuous Casting: The continuous casting process utilizes electromagnetic stirring in the mold, electromagnetic stirring at the end of solidification, and heavy reduction technology. The mold copper tube has internal dimensions of a 200mm×240mm rectangular billet cross-section. Casting is performed using an integral nozzle, with a continuous casting speed of 1.30m / min and a superheat of 17-23°C. The mold electromagnetic stirring current is 600A at a frequency of 3Hz, and the end electromagnetic stirring current is 500A at a frequency of 12Hz. A weak cooling process is used for the secondary cooling process, with a specific water volume of 0.28L / kg. The billet passes through 10 sets of straightening rollers, achieving a total heavy reduction of 11%. The reduction passes and reductions are 0 / 0 / 0 / 3 / 4 / 4 / 5 / 6 / 0 / 0mm, respectively. The final billet dimensions after heavy reduction are 178×246mm. Low-magnification examination of the billet reveals no central cracks, an equiaxed crystal area of 71%, and a central shrinkage cavity of level 0. Drilling tests reveal a carbon segregation index of 1.05.
[0045] Heating: The temperature of the second heating section of the walking beam heating furnace is 1010-1051°C, the temperature of the soaking section is 1066-1128°C, the heating time of the second heating section and the soaking section is 118 minutes in total, the furnace pressure is 21-29 Pa, and the residual oxygen content is 0.7-1.8%.
[0046] Rolling: After heating, the billets are descaled with high-pressure water at a pressure of 21 MPa to remove surface oxide scale. The descaled 178×246 mm rectangular billets are rolled into 160×160 mm intermediate billets using four headless blooming mills before entering a conventional roughing mill. The initial rolling temperature is 1038-1065°C, the finishing rolling temperature is 904-922°C, and the sizing temperature is 910-925°C.
[0047] Controlled cooling: spinning temperature 918-939℃, roller initial speed 1.10m / s, fan air volume 280000m 3 / h, with the air volumes of fans 1-8 set at 75% / 75% / 75% / 75% / 65% / 50% / 40% / 40% respectively, and the remaining fans turned off. The wire rod temperature at the 12th insulation cover was 561°C. The measured average cooling rates before, during, and after the phase transition were 24.2°C / s, 6.4°C / s, and 2.3°C / s, respectively.
[0048] Inspection results: 100% of the wire rod possesses martensite at level 0, 100% of central segregation at levels 0-1, 100% of grain boundary cementite at levels 0-1, a full decarburization depth of 0, a total decarburization depth of 20-30μm, 85% of sorbite, 0-0.03mm penetration depth of surface defects and scale, 0.011% wire rod inclusion purity, and a 35MPa difference in tensile strength within the same coil. In the production of φ0.30mm ultra-high-strength steel cord, the total breakage rate for wet-drawn wire was 0.7 times / ton, and the total breakage rate for stranded wire was 1.7 times / ton.
[0049] Comparative Example 1: Chemical composition of wire rod: by mass percentage, C: 0.81%, Si: 0.27%, Mn: 0.43%, S: 0.007%, P: 0.009%, Al: 0.0018%, Ti: 0.0008%, O: 0.0014%, N: 0.0029%, and the rest are Fe and unavoidable impurity elements.
[0050] Hot metal pretreatment: Hot metal is used and pre-desulfurized, with S content of 0.004% and Ti content of 0.027% entering the furnace.
[0051] Converter smelting: All scrap steel is self-produced clean scrap steel, with 34 tons added. High-carbon technology is used, and the steel produced has a C: 0.17%, O: 0.045%, P: 0.009%, and S: 0.008%.
[0052] Refining: LF refining uses magnesium-carbon refractory materials and low-aluminum, low-titanium alloy auxiliary materials to reduce alumina and titanium inclusions. Low-basicity slag is used to promote plasticization of inclusions, with a basicity of 0.8. The argon flow rate during soft blowing is 58 L / min, and the soft blowing time is 34 minutes.
[0053] Continuous casting: Electromagnetic stirring is used in the mold and at the end of solidification during the continuous casting process. The internal dimensions of the mold copper tube are 160mm×160mm in cross-section, and an integral nozzle is used for casting. The continuous casting speed is 1.80m / min, and the superheat is 21-28°C. The electromagnetic stirring current of the mold is 300A, the frequency is 3.5Hz, and the electromagnetic stirring current of the end is 500A, the frequency is 10Hz. The secondary cooling process adopts a strong cooling process with a specific water volume of 1.28L / kg. Low-magnification inspection of the ingot shows no intermediate cracks, the area of the equiaxed crystal zone accounts for 58%, and the central shrinkage cavity is all level 1.0. Using the drilling method for inspection, the carbon segregation index of the continuous casting ingot is 1.18.
[0054] Heating: The temperature of the second heating section of the walking beam heating furnace is 970-1064℃, the temperature of the soaking section is 1066~1120℃, the heating time of the second heating section and the soaking section is 66min in total, the furnace pressure is 12-27Pa, and the residual oxygen content is 0.9-3.5%.
[0055] Rolling: After heating, the steel billet is descaled by high-pressure water to remove surface iron oxide scale. The descaling pressure is 12MPa, the starting rolling temperature is 1018-1074℃, the finishing rolling temperature is 902-923℃, and the sizing temperature is 908-919℃.
[0056] Controlled cooling: spinning temperature 887-909℃, roller initial speed 1.10m / s, fan air volume 280000m 3The cooling rate was set at 23.2°C / s before, 10.3°C / s during, and 5.3°C / s after the phase change.
[0057] Inspection results: 95% of the wire rod possesses martensite at level 0, and 5% at levels 1-3; 80% of the center segregation at levels 0-1, and 20% at levels 1.5-2.0; 90% of the grain boundary cementite at levels 0-1, and 10% at levels 2-3; the full decarburization depth is 0, the total decarburization depth is 20-30μm, the proportion of sorbite is 85%, the depth of surface defects and scale penetration is 0-0.05mm, the wire rod inclusion purity is 0.025%, and the tensile strength difference within the same turn is 45MPa. In the production of φ0.30mm ultra-high-strength steel cord for a customer, the total breakage rate for wet-drawing is 1.3 times / ton, and the total breakage rate for stranding is 4.2 times / ton.
[0058] Comparative Example 2: Chemical composition of wire rod: by mass percentage, C: 0.83%, Si: 0.28%, Mn: 0.42%, S: 0.008%, P: 0.010%, Al: 0.0016%, Ti: 0.0009%, O: 0.0012%, N: 0.0027%, and the rest are Fe and unavoidable impurity elements.
[0059] Hot metal pretreatment: Hot metal is used and pre-desulfurized, with S: 0.005% and Ti: 0.024% in the hot metal entering the furnace.
[0060] Converter smelting: All scrap steel is self-produced clean scrap steel, with 32 tons added. High-carbon technology is used, and the steel produced has C: 0.16%, O: 0.044%, P: 0.008%, and S: 0.009%.
[0061] Refining: LF refining uses magnesium-carbon refractory materials and low-aluminum, low-titanium alloy auxiliary materials to reduce alumina and titanium inclusions. Low-basicity slag is used to promote plasticization of inclusions, with a basicity of 0.9. The argon flow rate during soft blowing is 59 L / min, and the soft blowing time is 38 minutes.
[0062] Continuous Casting: Electromagnetic stirring is used in the mold and at the end of solidification during the continuous casting process. The internal dimensions of the mold copper tube are 160mm×160mm in cross-section, and an integral nozzle is used for casting. The continuous casting speed is 1.80m / min, and the superheat is 22-27°C. The electromagnetic stirring current in the mold is 300A, the frequency is 3.5Hz, and the electromagnetic stirring current at the end is 500A, the frequency is 10Hz. The secondary cooling process uses a forced cooling process with a specific water volume of 1.28L / kg. Low-magnification inspection of the ingot shows no intermediate cracks, the equiaxed crystal area accounts for 61%, and the central shrinkage cavity is at the 1.0-1.5 level. Using the drilling method for inspection, the carbon segregation index of the continuous casting ingot is 1.23.
[0063] Heating: The temperature of the second heating section of the walking beam heating furnace is 980-1052°C, the temperature of the soaking section is 1071-1135°C, the heating time of the second heating section and the soaking section is 68 minutes in total, the furnace pressure is 10-35Pa, and the residual oxygen content is 1.0-4.8%.
[0064] Rolling: After heating, the steel billet is descaled by high-pressure water to remove surface iron oxide scale. The descaling pressure is 12MPa, the starting rolling temperature is 1010-1064℃, the finishing rolling temperature is 905-921℃, and the sizing temperature is 907-918℃.
[0065] Controlled cooling: Spinning temperature 885-919°C, initial roller speed 1.10 m / s, fan volume 280,000 m³ / h, airflow settings for fans #1-9 at 75% / 75% / 75% / 75% / 65% / 65% / 60% / 50% / 40%, respectively. All other fans were off, and all insulation covers were open. The measured average cooling rates before, during, and after the phase transition were 21.4°C / s, 9.8°C / s, and 4.6°C / s, respectively.
[0066] Inspection results: 95% of the wire rod had martensite at level 0, and 5% at levels 1-3; 75% of the center segregation had level 0-1, and 25% had level 1.5-2.0; 85% of the grain boundary cementite had level 0-1, and 15% had level 2-3; the full decarburization depth was 0, the total decarburization depth was 10-30μm, the proportion of sorbite was 85%, the depth of surface defects and scale penetration was 0-0.04mm, the wire rod inclusion purity was 0.034%, and the tensile strength difference within the same coil was 40MPa. In the production of φ0.30mm ultra-high-strength steel cord for a customer, the total breakage rate for wet-drawing was 1.5 breaks / ton, and the total breakage rate for stranding was 4.8 breaks / ton.
[0067] Comparative Example 3: Chemical composition of wire rod: by mass percentage, C: 0.82%, Si: 0.26%, Mn: 0.43%, S: 0.008%, P: 0.009%, Al: 0.0018%, Ti: 0.0007%, O: 0.0014%, N: 0.0032%, and the rest are Fe and unavoidable impurity elements.
[0068] Hot metal pretreatment: Hot metal is used and pre-desulfurized, with S content of 0.004% and Ti content of 0.028% entering the furnace.
[0069] Converter smelting: All scrap steel is self-produced clean scrap steel, with 33 tons added. High-carbon technology is used, and the steel produced has C: 0.18%, O: 0.038%, P: 0.009%, and S: 0.006%.
[0070] Refining: LF refining uses magnesium-carbon refractory materials and low-aluminum, low-titanium alloy auxiliary materials to reduce alumina and titanium inclusions. Low-basicity slag is used to promote plasticization of inclusions, with a basicity of 0.9. The argon flow rate during soft blowing is 56 L / min, and the soft blowing time is 42 minutes.
[0071] Continuous Casting: Electromagnetic stirring is used in the mold and at the end of solidification during the continuous casting process. The internal dimensions of the mold copper tube are 160mm×160mm in cross-section, and an integral nozzle is used for casting. The continuous casting speed is 1.80m / min, and the superheat is 24-29°C. The electromagnetic stirring current in the mold is 300A, the frequency is 3.5Hz, and the electromagnetic stirring current at the end is 500A, the frequency is 10Hz. The secondary cooling process uses a forced cooling process with a specific water volume of 1.28L / kg. Low-magnification inspection of the ingot shows no intermediate cracks, the equiaxed crystal area accounts for 63%, and the central shrinkage cavity is at the 1.0-1.5 level. Using the drilling method for inspection, the carbon segregation index of the continuous casting ingot is 1.21.
[0072] Heating: The temperature of the second heating section of the walking beam heating furnace is 974-1043℃, the temperature of the soaking section is 1077~1148℃, the heating time of the second heating section and the soaking section is 65 minutes in total, the furnace pressure is 8-32Pa, and the residual oxygen content is 0.9-4.5%.
[0073] Rolling: After heating, the steel billet is descaled by high-pressure water to remove surface iron oxide scale. The descaling pressure is 12MPa, the starting rolling temperature is 1026-1072℃, the finishing rolling temperature is 903-926℃, and the sizing temperature is 907-924℃.
[0074] Controlled cooling: spinning temperature 889-917℃, roller initial speed 1.10m / s, fan air volume 280000m 3The cooling rate was set at 22.8°C / s before, 8.7°C / s during, and 5.6°C / s after the phase change.
[0075] Inspection results: Wire rod martensite accounted for 95% at grade 0 and 5% at grades 1-3; central segregation accounted for 80% at grades 0-1 and 20% at grades 1.5-2.0; grain boundary cementite accounted for 90% at grades 0-1 and 10% at grades 2-3; the full decarburization depth was 0, the total decarburization depth was 10-30μm, the sorbite proportion was 85%, the surface defect and scale penetration depth was 0-0.04mm, the wire rod inclusion purity was 0.031%, and the tensile strength difference within the same turn was 40MPa. In the production of φ0.30mm ultra-high-strength steel cord for a customer, the total breakage rate for wet-drawing was 1.4 times / ton, and the total breakage rate for stranding was 3.8 times / ton.
[0076] The test results of Examples 1-3 and Comparative Examples 1-3 are shown in Table 1 below.
[0077]
[0078] Those skilled in the art will understand that the discussion of any of the above embodiments is merely illustrative and is not intended to limit the scope of the present invention to these examples. Within the spirit and principles of the present invention, the technical features of the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and many other variations exist for the various aspects of the present invention described above, which are not provided in detail for the sake of clarity. Any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention.
Claims
1. A production method for inhibiting martensitic transformation in a grade 80 cord steel wire rod, characterized in that: The method comprises the following steps: molten iron pretreatment → converter smelting → LF refining → continuous casting → heating → controlled rolling → controlled cooling; the continuous casting process adopts electromagnetic stirring combined with the heavy pressure reduction process of the cast billet, and the total reduction under heavy pressure is controlled to reach 9-11%, and the carbon segregation index of the continuous casting billet is 0.98-1.08; the controlled rolling adopts the method of adding a head-off billet opening machine in front of the rough rolling mill, first rolling the cast billet into an intermediate billet, and then entering the one-fire direct rolling process of the rough rolling mill; in the controlled cooling process, the cooling rates before, during and after the phase change are controlled to be 20-25°C / s, 3-8°C / s and ≤3°C / s respectively.
2. The method for suppressing martensitic transformation in a grade 80 cord steel wire rod according to claim 1, characterized in that: During the continuous casting process, the continuous casting speed is controlled at 1.25-1.35m / min, and the superheat is controlled at 15-25°C; the current of the electromagnetic stirring of the crystallizer is 580-620A, the frequency is 2-4Hz, the current of the terminal electromagnetic stirring is 490-510A, and the frequency is 11-13Hz; the secondary cooling adopts a weak cooling process, and the specific water volume is controlled at 0.25-0.30L / kg; the area of the equiaxed crystal zone of the ingot accounts for 65-75%, and the central shrinkage cavity is level 0-0.
5.
3. The method for suppressing martensitic transformation in a grade 80 cord steel wire rod according to claim 1, characterized in that: In the controlled rolling process, the descaling pressure is controlled to be ≥20MPa, 4 head-dropping slab opening machines are added before the rough rolling mill, the starting rolling temperature is 1020-1120°C, the finishing rolling temperature is 900-930°C, and the sizing temperature is 900-930°C.
4. The method for suppressing martensitic transformation in a grade 80 cord steel wire rod according to claim 3, characterized in that: After heavy pressing, the size of the cast billet is a rectangular billet of 182×244-178×246mm. During the controlled rolling process, 4 headless billet opening machines are used to roll the 182×244-178×246mm rectangular billet into an intermediate billet of 160×160mm, and then the billet enters the rough rolling unit for rolling.
5. The method for suppressing martensitic transformation in grade 80 cord steel wire rod according to claim 1, characterized in that: During the controlled cooling process, the wire rod spinning temperature is controlled at 915-945°C, the initial roller speed is 1.10m / s, and the rated air volume of the fan is 280000m 3 / h, the air volume of the first 4 fans is 75% of the rated air volume of the fan, the air volume of the 5th fan is 65% of the rated air volume of the fan, the air volume of the 6th fan is 50% of the rated air volume of the fan, the air volume of the 7th-8th fans is 40% of the rated air volume of the fan, and the remaining fans are turned off. When the wire rod temperature drops below 580℃, the thermal insulation cover is added.
6. The method for suppressing martensitic transformation in a grade 80 cord steel wire rod according to claim 1, characterized in that: The molten iron pretreatment adopts molten iron and undergoes a pre-desulfurization process to control S≤0.005% and Ti≤0.03% in the molten iron entering the furnace.
7. The method for suppressing martensitic transformation in a grade 80 cord steel wire rod according to claim 1, characterized in that: The converter smelting adopts a high carbon drawing method to control the steel output C≥0.15%, O≤0.050%, P≤0.008%, and S≤0.010%.
8. The method for suppressing martensitic transformation in a grade 80 cord steel wire rod according to claim 1, characterized in that: In the LF refining process, a double slag method is used to promote plasticization of inclusions. The first slag making controls the slag basicity to be 2.5-3.0; the second slag making controls the slag basicity to be 0.7-0.9; the argon flow rate during soft blowing is 55-58 L / min, and the soft blowing time is ≥60 min.
9. The method for suppressing martensitic transformation in a grade 80 cord steel wire rod according to claim 1, characterized in that: The temperature of the second heating section used in the heating is 950-1080°C, and the temperature of the soaking section is 1060-1160°C.
10. The method for suppressing martensitic transformation in a grade 80 cord steel wire rod according to claim 1, characterized in that: The chemical composition of the 80-grade cord steel wire rod includes, by mass percentage, C: 0.80-0.85%, Si: 0.25-0.30%, Mn: 0.40-0.45%, S≤0.008%, P≤0.010%, Al≤0.002%, Ti≤0.001%, O≤0.0015%, N≤0.0035%, and the rest are Fe and unavoidable impurity elements.
Citation Information
Patent Citations
Method for controlling network cementites in ultrahigh-carbon steel wire cord
CN105256119A
80-grade tire cord steel wire rod being suitable for acidic-pickling descaling and production method of same
CN105316573A
Control method for segregation and net carbon of 86-grade high-strength cord steel wire rod
CN112359277A
Steel for steel cord with tensile strength larger than or equal to 4000 MPa and production method
CN114182164A
Alloying ultrahigh-strength high-carbon hard wire steel high-speed wire rod rolling method
CN116351866A
Cited By
High-plasticity extra-high-strength tire cord steel wire rod and production process thereof
CN122344686A